Noise Characteristics and Sound Pressure Level Prediction of Loggia Balcony in Apartment - Afif Fajar Zakariya; Ima Defiana; Teddy Badai Samodra (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
Many residential areas are in the street class with high noise, including the apartment. Noise is often overlooked when it will have an impact on the health of residents. The balcony design in apartments can capture and even reduce noise, so this needs to be further investigated; the most widely used balcony in the apartment is a loggia type balcony. To find out the noise level of a place from a particular source such as traffic noise can be done by direct measurement. Knowing the noise level ratio, the method taken is field measurement, simulation, and mathematical calculations. The method of measuring the field using the Gunawangsa Manyar Apartment object by measuring noise levels carried out for 24 hours on the apartment's balcony, the noise level simulation method was carried out with I-Simpa, and the calculation method used a mathematical model. The results obtained are two types of noise on the apartment balcony, namely vehicle noise is steady, and vehicle noise is impulsive with noisy air-conditioner. The comparison of field measurements with simulation methods and calculations shows a high relationship so that the I-Simpa simulation method and calculation can be used to predict the desired noise level on a particular floor.